Mathematical modeling of vaporization during laser-induced thermotherapy in liver tissue - Sebastian Blauth; Frank Hübner; Christian Leithäuser; Norbert Siedow; Thomas J. Vogl (Journal of Mathematics in Industry, 2020)
Abstract Laser-induced thermotherapy (LITT) is a minimally invasive method causing tumor destruction due to heat ablation and coagulative effects. Computer simulations can play an important role to assist physicians with the planning and monitoring of the treatment. Our recent study with ex-vivo porcine livers has shown that the vaporization of the water in the tissue must be taken into account when modeling LITT. We extend the model used for simulating LITT to account for vaporization using two different approaches. Results obtained with these new models are then compared with the measurements from the original study.